The Existence and Governance of Waqf in Creating Public Value at Pondok Pesantren Darussalam Blokagung Banyuwangi - Habibulloh; Abubakar Eby Hara; Mahfudz Sidiq; Hadi Prayitno (GoAcademica Research & Publishing, 2023)
This study aims to explain waqf governance in maintaining its existence. Waqf can create public value by using management, public service, and governance approaches to waqf policies. This illustrates the existence of waqf in the middle of the public administration process with the governance model developed by Nadzir. This type of phenomenological research with a qualitative approach based on the philosophy of postpositivism with primary and secondary data through purposive sampling and snowball. Data collection techniques use observation, in-depth interviews, documentation, and literature studies. The results and discussion of the research paradigm are naturalistic in nature, because it allows finding the meaning of each phenomenon, both regarding local wisdom, traditional, emic, ethical, abstract (moral values), and theories of the subjects studied. The existence and management of waqf in Islamic boarding schools is a form of good waqf governance (good waqf givenance). Good waqf governance is built on three main pillars, namely first; waqf values in Islamic boarding schools which originate from the Koran, al-Hadith, and the yellow book, for example; attitude of Tawadhu', Ikhlas, Qana'ah, Tabarruk, Innovative, and Amanah as public values (moral values). Second; waqf governance models that are in accordance with the objectives and functions of waqf, namely to provide benefits to the surrounding community, both directly and continuously. Third; waqf governance is supported by a legal basis both spiritual and public administration (government).